2006
DOI: 10.1136/vr.158.5.155
|View full text |Cite
|
Sign up to set email alerts
|

Methicillin‐resistant Staphylococcus aureus isolated from a veterinary surgeon and five dogs in one practice

Abstract: Methicillin-resistant Staphylococcus aureus (MRSA) was isolated from five dogs with wound discharges after surgical procedures at a veterinary practice, and MRSA with similar molecular and phenotypic characteristics was isolated from the nares of one veterinary surgeon in the practice. The pulsed-field gel electrophoresis patterns of all the isolates were indistinguishable from each other and from the most common human isolates of MRSA in Ireland.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(50 citation statements)
references
References 24 publications
0
48
0
2
Order By: Relevance
“…Several studies have implicated hospital surfaces contaminated with nosocomial pathogens, including MRSA, in the dissemination of hospital-acquired infections (Rampling et al 2001, Schultsz et al 2003, Hota 2004, Kramer et al 2006, Sexton et al 2006, Boyce 2007, Weber et al 2010, Otter et al 2011. Paralleling these are reports of the increasing role of MRSA in nosocomial infections in veterinary settings (Seguin et al 1999, Leonard, et al 2006, Weese et al 2007, Benedict et al 2008, McLean and Ness 2008, van Duijkeren et al 2010. A recent study of veterinary teaching hospitals accredited by the American Veterinary Medicine Association (AVMA) found that MRSA was the second most common pathogen (13/31, 42%) associated with nosocomial outbreaks (Benedict et al 2008).…”
Section: Introductionmentioning
confidence: 76%
“…Several studies have implicated hospital surfaces contaminated with nosocomial pathogens, including MRSA, in the dissemination of hospital-acquired infections (Rampling et al 2001, Schultsz et al 2003, Hota 2004, Kramer et al 2006, Sexton et al 2006, Boyce 2007, Weber et al 2010, Otter et al 2011. Paralleling these are reports of the increasing role of MRSA in nosocomial infections in veterinary settings (Seguin et al 1999, Leonard, et al 2006, Weese et al 2007, Benedict et al 2008, McLean and Ness 2008, van Duijkeren et al 2010. A recent study of veterinary teaching hospitals accredited by the American Veterinary Medicine Association (AVMA) found that MRSA was the second most common pathogen (13/31, 42%) associated with nosocomial outbreaks (Benedict et al 2008).…”
Section: Introductionmentioning
confidence: 76%
“…Several reports have shown that MRSA can also spread in veterinary hospital settings from humans to animals (reverse zoonosis) and from animals to humans (zoonosis), and has the ability to survive in the environment (Seguin et al 1999, Van Duijkeren et al 2004, Weese et al 2004, Baptiste et al 2005, O'Mahony et al 2005, Leonard et al 2006). Not only is this a concern from the point of view of nosocomial transmission in veterinary hospitals and the negative effect on animal health, the presence of MRSA in veterinary settings is also a growing occupational health issue for the veterinary community, where staff and veterinarians could be routinely exposed to this pathogen (Benedict et al 2008).…”
mentioning
confidence: 99%
“…S. aureus can give rise to a wide diversity of suppurative infections in animals. In line with that, MRSA have been isolated from diverse skin and STIs including abscesses, dermatitis, postoperative wound infections, and intravenous catheter or surgical implant infections [1,55,57,73,83,86,[87][88][89][90]. Morris et al [91] reported that MRSA were significantly more frequently associated with deep pyoderma in dogs than other strains of S. aureus.…”
Section: Occurrence In Companion Animalsmentioning
confidence: 89%
“…In a retrospective case-control study at three veterinary referral hospitals significant risk factors for the acquisition of a MRSA infection compared to a MSSA infection was the presence of a urinary catheter or a joint infection [93]. Invasive procedures, including the presence of foreign material such as suture material, orthopaedic implants, urinary catheters, central venous lines and chest drains appear to be associated with the persistence of MRSA infections [88,95]. Other identified risk factors associated with SSIs in general, but highly relevant in particular for staphylococci infections, include : improper surgical site clipping and aseptic preparation before surgery, duration of surgery, duration of anaesthesia, emergency vs. daytime surgery, surgical tissue handling, number of persons present in the operating room, and total length of hospital stay [95].…”
Section: Risk Factors For Colonization and Infection In Companion Animentioning
confidence: 99%